Mature placental teratoma: A rare case with emphasis on histopathological diagnosis - Mahajan, Niharika; Tiwana, Kanwardeep Kaur; Arora, Shagun (Indian Journal of Case Reports, 2026)
Mature placental teratoma is an exceptionally rare non-trophoblastic tumor, with fewer than 40 cases reported in the literature. We report a case of an 18-year-old primigravida with Rh-negative pregnancy who presented with intrauterine fetal demise at 38 weeks and 4 days of gestation. Gross examination of the placenta revealed a well-circumscribed, white, lobulated mass measuring 2 × 1.5 × 1 cm within the membranes. Microscopic examination demonstrated a tumor composed of mature derivatives of multiple germ layers, including keratinized stratified squamous epithelium with adnexal structures, mature cartilage, adipose tissue, and nerve bundles. No immature neuroepithelial elements or axial skeletal structures were identified. A diagnosis of mature placental teratoma was established. This case highlights the diagnostic importance of histopathological evaluation in distinguishing placental teratoma from fetus acardius amorphous and other placental masses.